Proprotein Convertase Subtilisin Kexin Type 9 Inhibition for Autosomal Recessive Hypercholesterolemia—Brief Report. Issue 8 (August 2016) - Thedrez, Aurélie; Sjouke, Barbara; Passard, Maxime; Prampart-Fauvet, Simon; Guédon, Alexis; Croyal, Mikael; Dallinga-Thie, Geesje; Peter, Jorge; Blom, Dirk; Ciccarese, Milco; Cefalù, Angelo B.; Pisciotta, Livia; et al.
Abstract : Objective—: Proprotein convertase subtilisin kexin type 9 (PCSK9) inhibitors lower low-density lipoprotein (LDL) cholesterol in the vast majority of patients with autosomal dominant familial hypercholesterolemia. Will PCSK9 inhibition with monoclonal antibodies, in particular alirocumab, be of therapeutic value for patients with autosomal recessive hypercholesterolemia (ARH)? Approach and Results—: Primary lymphocytes were obtained from 28 genetically characterized ARH patients and 11 controls. ARH lymphocytes treated with mevastatin were incubated with increasing doses of recombinant PCSK9 with or without saturating concentrations of alirocumab. Cell surface LDL receptor expression measured by flow cytometry and confocal microscopy was higher in ARH than in control lymphocytes. PCSK9 significantly reduced LDL receptor expression in ARH lymphocytes albeit to a lower extent than in control lymphocytes (25% versus 76%, respectively), an effect reversed by alirocumab. Fluorescent LDL cellular uptake, also measured by flow cytometry, was reduced in ARH lymphocytes compared with control lymphocytes. PCSK9 significantly lowered LDL cellular uptake in ARH lymphocytes, on average by 18%, compared with a 46% reduction observed in control lymphocytes, an effect also reversed by alirocumab. Overall, the effects of recombinant PCSK9, and hence of alirocumab, on LDL receptor expression and function were significantly less pronounced in ARH than in control cells. Conclusions—: PCSK9 inhibition with alirocumab on top of statin treatment has the potential to lower LDL cholesterol in some autosomal recessive hypercholesterolemia patients. Abstract : Supplemental Digital Content is available in the text.